2010
DOI: 10.1210/en.2010-0590
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Amylin-Mediated Body Weight Loss in Estradiol-Deficient Diet-Induced Obese Rats

Abstract: In rodents, ovariectomy (OVX) elicits weight gain and diminished responsiveness to homeostatic signals. Here we characterized the response of obese OVX rats to peripheral amylin. Rats received sham surgery (SHAM), OVX, or OVX with hormonal replacement (17β-estradiol, 2 μg per 4 d; OVX+E) and were infused with vehicle or amylin (50 μg/kg · d) for 28 d. Amylin reduced body weight (5.1 ± 1.1%) and food intake (10.9 ± 3.4%) in SHAM rats but was twice as efficacious in OVX rats in reducing weight (11.2 ± 1.9%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 42 publications
5
56
1
Order By: Relevance
“…We recently explored whether estradiol signaling affected the weight regulatory and metabolic effects of amylin agonism (see also Fig. 5) (Trevaskis et al, 2010c). We observed a surprising approximately 2-fold increase in amylin's weight-lowering efficacy in a state of estradiol deficiency [DIO ovariectomized (OVX) rat model] compared with sham-operated controls.…”
Section: Identifying Amylin Agonist-responsive Populations In Precmentioning
confidence: 99%
“…We recently explored whether estradiol signaling affected the weight regulatory and metabolic effects of amylin agonism (see also Fig. 5) (Trevaskis et al, 2010c). We observed a surprising approximately 2-fold increase in amylin's weight-lowering efficacy in a state of estradiol deficiency [DIO ovariectomized (OVX) rat model] compared with sham-operated controls.…”
Section: Identifying Amylin Agonist-responsive Populations In Precmentioning
confidence: 99%
“…Two tests of the estrogenic modulation of amylin's eating-inhibitory effects produced opposite results. Trevaskis et al (742) reported that cyclic estradiol treatment markedly reduced the potency of chronic subcutaneous infusion of 50 g·kg Ϫ1 ·day Ϫ1 amylin to reduce eating and body weight in ovariectomized rats. On the other hand, Asarian et al (14) found that in acute eating tests, estradiol cyclically increased the satiating potency of exogenous amylin and the desatiating potency of amylin antagonism.…”
Section: R1236 Sex Differences In the Physiology Of Eatingmentioning
confidence: 99%
“…Recently, Trevaskis and colleagues [188] (but see also [189]) reported that the action of (chronic) amylin on eating and body weight was stronger in ovariectomized rats that lack estradiol than in control rats or in ovariectomized rats receiving physiological estradiol replacement therapy; amylin's effect to reduce eating and body weight was about double. This was surprising, because most previous (acute) studies had reported an enhanced effect of satiating hormones by estradiol and not by the lack of it [181,185,187].…”
Section: Therapeutic Potential Of Amylin In Anti-obesity Therapymentioning
confidence: 99%